The Era of Society 5.0 as the unification of humans and technology: A literature review on materialism and existentialism - Melinda Rahmawati; Ahmad Ruslan; Desvian Bandarsyah (Jurnal Sosiologi Dialektika, 2021)
The Industrial Revolution 4.0 brings society in fast-paced change. Technology and social media emerge not only as a means of communication and accessibility of modern society, but also as a means of mass news spread and provocation. When society and technology coexist, technology is able to drive people to have accessibility without time limits. The objective of this study is to describe the overview of the Era of Society 5.0 seen from the perspectives of materialism and existentialism in social sciences. The research method used was descriptive qualitative with literature review analysis which specifically discussed modern society and the idea of materialism and existentialism. The results of this study showed that the Era of Society 5.0 has indeed become an era of the unification of humans and technology. Technology has become a necessity that must be fulfilled by all people. The perspectives of materialism and existentialism view it as a critical period because society is vulnerable to division if it is not directed properly. This study concluded that the Era of Society 5.0 is described as a period when humans and their mindsets are trapped between material needs and the desire for existence. Technology that is interconnected and accessed without limits presents a complex situation. The streams of materialism and existentialism provide an overview of the situation of society in two related sides.